The characterization of Klebsiella pneumoniae associated with neonatal sepsis in low- and middle-income countries to inform vaccine design - Francesca Nonne; Mariagrazia Molfetta; Gianina Florentina Belciug; Martina Carducci; Virginia Cianchi; Casey Zakroff; Salvatore Durante; Caroline Zellmer; Stephen Baker; Thomas D. Stanton; Kathryn E. Holt; Kelly Wyres; et al. (Communications Biology)
Abstract Klebsiella pneumoniae is the leading cause of neonatal sepsis, strongly associated to antimicrobial resistance, with no vaccine available. K-antigens (KAg) have been identified as potential targets, but their diversity makes vaccine development challenging. Alternatively, the use of subcapsular O-antigens (OAg) raises questions about antibodies accessibility. We characterized clinical isolates from the BARNARDS study, designed to identify the burden of neonatal sepsis in low-middle income countries. Genomic prediction was verified through structural analysis of polysaccharides. Antibodies generated against common KAg and OAg bound all homologous organisms, regardless of specific polysaccharide structural features. Interestingly, anti-KAg antibodies exhibited bactericidal activity against a comparable number of isolates as anti-OAg antibodies. There was no association between polysaccharide characteristics and K. pneumoniae susceptibility to killing. Antibody cross-reactivity among different KAg was observed, together with extensive cross-reactivity among OAg antibodies. This study aids in defining an optimal vaccine composition to prevent neonatal sepsis caused by K. pneumoniae.